Diversity and population connectivity of members of the family Eunicidae inhabiting deep-water corals in the North Atlantic - Carlota Gracia-Sancha; Nicolai Roterman; Michelle L. Taylor; Kerry L. Howell; Alex D. Rogers; Sofía Ruiz-Cano; Sergi Taboada (Molecular Phylogenetics and Evolution, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Genomic Connectivity and Adaptation Signals of the Freshwater Sponge Ephydatia muelleri Across Its Distribution - Laura de la Cruz‐Castillejo; Robert Cassidy; Konstantina Mitsi; Carles Galià‐Camps; Ana Benítez‐López; Carlota Gracia‐Sancha; Jose Lorente‐Sorolla; Almudena Álvarez‐Fernández; Rocío Mozo; Stephen Kolomyjec; Scott Nichols; Renata Manconi; et al. (Journal of Biogeography, 2026)
Aim Genetic connectivity and local adaptation were examined across the distribution of the freshwater sponge Ephydatia muelleri . Because it occupies an exceptional breadth of freshwater environments across a broad geographic range, this species offers key insights into biogeographic processes shaping genetic structure and adaptation in inland waters. Location Freshwater habitats across North America, Europe and Asia. Taxon Freshwater sponges (Porifera, order Spongillida). Methods A total of 106 individuals were sampled from 11 localities across three continents. Double‐digest RADseq was used to generate genome‐wide SNP data, resulting in 3114 putatively neutral SNPs for analyses of population structure and connectivity and 115 candidate SNPs potentially under selection for assessing signatures of local adaptation to environmental variables such as light and temperature. Results Neutral loci revealed low connectivity and strong genetic differentiation among regions, with two major genetic clusters corresponding to North America and Eurasia. Loci under selection indicated polygenic adaptation to environmental gradients of light and temperature and evidence of selection on gene regulatory processes. Patterns of genetic structure are consistent with the monopolisation hypothesis, suggesting that historical processes, particularly range shifts and barriers associated with the Last Glacial Maximum, have had a stronger influence on current genetic structure than ongoing gene flow. Main Conclusions Ephydatia muelleri populations show limited dispersal and strong historical imprints on genetic structure but also exhibit adaptive responses to local environmental variation. These findings highlight how monopolisation and historical climatic events shape freshwater invertebrate biogeography. Our study provides new insights into dispersal pathways, genetic plasticity and the resilience of freshwater sponges, with implications for the conservation of freshwater ecosystems.

Pyrolysis of agar-agar industry macroalgal waste for biofuel generation and high-performance adsorbents for pressurised gas storage - E. Ciurcina; L. Taboada-Ruiz; E. Fuente; S. Paniagua; L.F. Calvo; F. Suárez-García; M.Díaz Somoano; B. Ruiz (Journal of Environmental Chemical Engineering, 2025)

The Early Pennsylvanian transgressions in western Gondwana, the Pituil Formation as a reference in the Calingasta–Uspallata Basin - Osvaldo A. Conde; Gustavo A. Correa; María L. Balarino; Cristian A. Pardo; Arturo C. Taboada; Soledad Gouiric-Cavalli; Roberto R. Pujana (Sedimentary Geology, 2024)

Progress and challenges in valorisation of biomass waste from ornamental trees pruning through pyrolysis processes. Prospects in the bioenergy sector - L. Taboada-Ruiz; R. Pardo; B. Ruiz; M. Díaz-Somoano; L.F. Calvo; S. Paniagua; E. Fuente (Environmental Research, 2024)

Reinterpreting glacial deposits as a MTD ponding sediment gravity flows in the upper Mojón de Hierro Formation (Tepuel–Genoa Basin, Argentina) - Natalie B. McNall; John L. Isbell; Arturo C. Taboada; M. Alejandra Pagani; Eduardo Menozzo da Rosa (Sedimentary Geology, 2023)

Exploring the potential of conventional and flash pyrolysis methods for the valorisation of grape seed and chestnut shell biomass from agri-food industry waste - R. Pardo; L. Taboada-Ruiz; E. Fuente; B. Ruiz; M. Díaz-Somoano; L.F. Calvo; S. Paniagua (Biomass and Bioenergy, 2023)

Soil water availability and water absorption by maize in sodic soils with high water table - Federico J. Garello; Edmundo L. Ploschuk; Esteban M. Melani; Miguel A. Taboada (Field Crops Research, 2023)

Ocean carbon from space: Current status and priorities for the next decade - Robert J.W. Brewin; Shubha Sathyendranath; Gemma Kulk; Marie-Hélène Rio; Javier A. Concha; Thomas G. Bell; Astrid Bracher; Cédric Fichot; Thomas L. Frölicher; Martí Galí; Dennis Arthur Hansell; Tihomir S. Kostadinov; et al. (Earth-Science Reviews, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Variability of photosynthetic and related traits in maize and other summer crops in a temperate humid area - Lorena Álvarez-Iglesias; María I. Vales; Antonio M. De Ron; Ana P. Rodiño; Juan L. Tejada-Hinojoza; Alfredo Taboada; Pedro Revilla (Plant Physiology Reports, 2022)
Photosynthetic rate and water use efficiency (WUE) are crucial for the sustainable use of water in agriculture. Our objective was to analyze the variability of photosynthetic and related traits in maize ( Zea mays L.) and other summer crops in a temperate humid area. We evaluated photosynthetic parameters in maize for three years and compared them to pigeonpea and chickpea, adapted to arid environments, and pepper, tomato and common bean, as irrigated crops. Variability was significant in maize for most photosynthetic parameters and no consistent patterns of variability were found among genotypes. Compared to other crops, maize (C 4 crop) had the highest CO 2 assimilation and WUE, and the lowest stomatal conductance, substomatal CO 2 concentration, and transpiration. CO 2 assimilation was lowest for chickpea, stomatal conductance was highest for pigeonpea, substomatal CO 2 concentration was highest for tomato and pigeonpea, transpiration was highest for pigeonpea, and WUE was lowest for pigeonpea. Chickpea lacked variability for photosynthetic traits, while pigeonpea has the largest potential for improving photosynthetic traits. Net assimilation, conductance, and transpiration could be improved in common bean, and substomatal CO 2 concentration in pepper. Water Use Efficiency could be improved in some C 3 crops, but more genetic biodiversity has to be identified in maize.

Ceftazidime–avibactam treatment in bacteremia caused by OXA-48 carbapenemase-producing Klebsiella pneumoniae - O. Lima; A. Sousa; R. Longueira-Suárez; A. Filgueira; C. Taboada-Martínez; C. Portela-Pino; A. Nodar; F. Vasallo-Vidal; L. Martinez-Lamas; A. Pérez-Landeiro; M. Rubianes; MT. Pérez-Rodríguez (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Population structure of the fungus Sclerotinia sclerotiorum in common bean fields of Argentina - Carla L. Abán; Gisel Taboada; Yamila Spedaletti; Efraín Maita; Marta Z. Galván (European Journal of Plant Pathology, 2021)

An updated life‐history scheme for marine fishes predicts recruitment variability and sensitivity to exploitation - Colleen M. Petrik; Fernando González Taboada; Charles A. Stock; Jorge L. Sarmiento (Global Ecology and Biogeography, 2021)
Aim Patterns of population renewal in marine fishes are often irregular and lead to volatile fluctuations in abundance that challenge management and conservation efforts. Here, we examine the relationship between life‐history strategies and recruitment variability in exploited marine fish species using a macroecological approach. Location Global ocean. Time period 1950–2018. Major taxa studied Bony and cartilaginous fish. Methods Based on trait data for 244 marine fish species, we extend the established equilibrium–periodic–opportunistic ( E‐P‐O ) life‐history classification scheme objectively to include two additional emergent life‐history strategies: “bet‐hedgers” ( B ) and salmonic ( S ) strategists. The B strategists include rockfishes and other species inhabiting patchy benthic habitats with life histories that blend characteristics of E and P species; they combine very long life spans with elevated investments in both parental care and fecundity. The S strategists mainly comprise salmonids that share life‐history characteristics with E and O species: elevated investments in parental care reminiscent of E strategists, but with reduced fecundity and short life spans characteristic of O species. We analysed how the E‐B‐P‐O‐S life‐history classification mapped onto patterns of recruitment variability observed in population time series data ( n = 156 species). Results Generalized linear models suggested that life‐history strategy explained a modest, yet significant amount of recruitment variability across species. Greater predictive power arose after controlling for increased recruitment variance associated with variable fishing pressure, with O strategists showing the strongest sensitivity. The B strategists were susceptible to exploitation in a similar manner to P stocks, but their longer times to maturity made them particularly vulnerable to overfishing. Main conclusions A broader recognition of the distinct ecology of salmonic and bet‐hedger groups is important when studying life‐history strategies in marine fish. More generally, our results stress the importance of considering life‐history strategies for understanding patterns of recruitment variability across fish stocks.

Implications of population connectivity studies for the design of marine protected areas in the deep sea: An example of a demosponge from the Clarion‐Clipperton Zone - Sergi Taboada; Ana Riesgo; Helena Wiklund; Gordon L. J. Paterson; Vasiliki Koutsouveli; Nadiezhda Santodomingo; Andrew C. Dale; Craig R. Smith; Daniel O. B. Jones; Thomas G. Dahlgren; Adrian G. Glover (Molecular Ecology, 2018)
The abyssal demosponge Plenaster craigi inhabits the Clarion‐Clipperton Zone ( CCZ ) in the northeast Pacific, a region with abundant seafloor polymetallic nodules with potential mining interest. Since P. craigi is a very abundant encrusting sponge on nodules, understanding its genetic diversity and connectivity could provide important insights into extinction risks and design of marine protected areas. Our main aim was to assess the effectiveness of the Area of Particular Environmental Interest 6 ( APEI ‐6) as a potential genetic reservoir for three adjacent mining exploration contract areas ( UK ‐1A, UK ‐1B and OMS ‐1A). As in many other sponges, COI showed extremely low variability even for samples ~900 km apart. Conversely, the 168 individuals of P. craigi, genotyped for 11 microsatellite markers, provided strong genetic structure at large geographical scales not explained by isolation by distance (IBD). Interestingly, we detected molecular affinities between samples from APEI ‐6 and UK ‐1A, despite being separated ~800 km. Although our migration analysis inferred very little progeny dispersal of individuals between areas, the major differentiation of OMS ‐1A from the other areas might be explained by the occurrence of predominantly northeasterly transport predicted by the HYCOM hydrodynamic model. Our study suggests that although APEI ‐6 does serve a conservation role, with species connectivity to the exploration areas, it is on its own inadequate as a propagule source for P. craigi for the entire eastern portion of the CCZ . Our new data suggest that an APEI located to the east and/or the south of the UK ‐1, OMS ‐1, BGR , TOML and NORI areas would be highly valuable.

Aluminum fractionation in acidic soils and river sediments in the Upper Mero basin (Galicia, NW Spain) - L. Palleiro; C. Patinha; M. L. Rodríguez-Blanco; M. M. Taboada-Castro; M. T. Taboada-Castro (Environmental Geochemistry and Health, 2018)

Winter‐mixing preconditioning of the spring phytoplankton bloom in the Bay of Biscay - Ricardo González‐Gil; Fernando González Taboada; Carlos Cáceres; John L. Largier; Ricardo Anadón (Limnology and Oceanography, 2018)
The spring phytoplankton bloom plays a key role in the dynamics of temperate and polar seas. Nevertheless, the mechanisms and processes behind these blooms remain a subject of considerable debate. We analyzed the influence of deep mixing during winter on the spring phytoplankton bloom in the Cantabrian Sea (southern Bay of Biscay). To this end, we combined long‐term physical and biogeochemical in situ data (1993–2012) and satellite observations (1997–2012). Deeper winter mixing led to higher nitrate and chlorophyll concentrations through the water column during the spring bloom. However, this effect was modified by short‐term variability in near‐surface stratification in spring. Winter‐mixing preconditioning also influenced different spring bloom metrics: deeper and later mixing in winter was followed by later blooms with a larger peak. In these enhanced blooms, nitrate was taken up at faster rates, indicating higher rates of phytoplankton production. Winters with weaker mixing (that led to weaker spring blooms) were associated with warmer surface temperatures. This relationship suggests that the multi‐decadal trend toward warmer surface temperatures in the Bay of Biscay may promote a decrease in the magnitude of the spring bloom, which could impact upper trophic levels and also deep carbon export in the future.

Mitochondrial genome and polymorphic microsatellite markers from the abyssal sponge Plenaster craigi Lim & Wiklund, 2017: tools for understanding the impact of deep-sea mining - Sergi Taboada; Nathan J. Kenny; Ana Riesgo; Helena Wiklund; Gordon L. J. Paterson; Thomas G. Dahlgren; Adrian G. Glover (Marine Biodiversity, 2018)

Local genes for local bacteria: Evidence of allopatry in the genomes of transatlantic Campylobacter populations - Ben Pascoe; Guillaume Méric; Koji Yahara; Helen Wimalarathna; Susan Murray; Matthew D. Hitchings; Emma L. Sproston; Catherine D. Carrillo; Eduardo N. Taboada; Kerry K. Cooper; Steven Huynh; Alison J. Cody; et al. (Molecular Ecology, 2017)
The genetic structure of bacterial populations can be related to geographical locations of isolation. In some species, there is a strong correlation between geographical distance and genetic distance, which can be caused by different evolutionary mechanisms. Patterns of ancient admixture in Helicobacter pylori can be reconstructed in concordance with past human migration, whereas in Mycobacterium tuberculosis it is the lack of recombination that causes allopatric clusters. In Campylobacter , analyses of genomic data and molecular typing have been successful in determining the reservoir host species, but not geographical origin. We investigated biogeographical variation in highly recombining genes to determine the extent of clustering between genomes from geographically distinct Campylobacter populations. Whole‐genome sequences from 294 Campylobacter isolates from North America and the UK were analysed. Isolates from within the same country shared more recently recombined DNA than isolates from different countries. Using 15 UK /American closely matched pairs of isolates that shared ancestors, we identify regions that have frequently and recently recombined to test their correlation with geographical origin. The seven genes that demonstrated the greatest clustering by geography were used in an attribution model to infer geographical origin which was tested using a further 383 UK clinical isolates to detect signatures of recent foreign travel. Patient records indicated that in 46 cases, travel abroad had occurred UK origin. Identification of biogeographical markers in Campylobacter genomes will contribute to improved source attribution of clinical Campylobacter infection and inform intervention strategies to reduce campylobacteriosis.

Anticipatory capacity in response to global change across an extreme elevation gradient in the Ica Basin, Peru - Rafael de Grenade; Joshua Rudow; Rossi Taboada Hermoza; Maria Elena Adauto Aguirre; Christopher A. Scott; Bram Willems; Jennifer L. Schultz; Robert G. Varady (Regional Environmental Change, 2017)

The Influence of Discharge, pH, Dissolved Organic Carbon, and Suspended Solids on the Variability of Concentration and Partitioning of Metals in a Rural Catchment - L. Palleiro; M. L. Rodríguez-Blanco; M. M. Taboada-Castro; M. T. Taboada-Castro (Water, Air, & Soil Pollution, 2013)

Climate Variability in NW Spain and its Relationship with Water Balance and Streamflow in a Small Headwater Catchment: Preliminary Results - M. L. Rodríguez-Blanco; M. M. Taboada-Castro; M. T. Taboada-Castro (Pure and Applied Geophysics, 2012)

Improved somatic embryogenesis of grapevine (Vitis vinifera) with focus on induction parameters and efficient plant regeneration - J. R. Vidal; J. Rama; L. Taboada; C. Martin; M. Ibañez; A. Segura; M. E. González-Benito (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Optimization tools and simulation methods for designing and evaluating a mining operation - F. G. Bastante; J. Taboada; L. Alejano; E. Alonso (Stochastic Environmental Research and Risk Assessment, 2008)

Links between circulation weather types and teleconnection patterns and their influence on precipitation patterns in Galicia (NW Spain) - M. N. Lorenzo; J. J. Taboada; L. Gimeno (International Journal of Climatology, 2008)
An automated version of the Lamb weather type classification scheme was used to study the relationship between atmospheric circulation patterns and rainfall in the northwestern part of the Iberian Peninsula, which is an important area of crossing influences of the different teleconnection patterns of the Northern Hemisphere. We calculated the correlation between the most important teleconnection patterns that affect this area and the different types of weather circulation. In this area, anticyclone weather types are the most frequent in any part of the year. The frequency of occurrence of W and SW situations is also significant in autumn and winter. The correlation between weather types (WT) and teleconnection patterns showed that the North Atlantic Oscillation (NAO) index has significant correlations only in winter, while other patterns, such as the Eastern Atlantic (EA), have significant correlations in the other seasons. As a result of these correlations, the EA is a more relevant pattern than the NAO for describing the Galician climate throughout the year. We also calculated correlations between the North Hemisphere Annular Mode (NAM) and the different types of weather types. The NAM shows significant correlations throughout the year. Hence, the NAM is more relevant than the NAO, which is its local manifestation. Copyright © 2007 Royal Meteorological Society

Effects of dietary L-arginine supplementation on serum lipids and intestinal enzyme activities in diabetic rats - L. Míguez; G. Mariño; B. Rodríguez; C. Taboada (Journal of Physiology and Biochemistry, 2004)

Structural stability changes in a grazed grassland natraquoll of the Flooding Pampa (Argentina) - Miguel A. Taboada; Raúl S. Lavado; Héctor Svartz; Andrea M. L. Segat (Wetlands, 1999)